HUBUNGAN ASAP ROKOK TERHADAP TERJADINYA HIPERTENSI PADA IBU HAMIL DI DESA BRANGKAL BOJONEGORO - Astri Meidah Setiawati (Universitas Jember, 2019)
Cigarette exposure is one factor in the occurrence of hypertension and can increase blood pressure both for pregnant women and not. Hypertension is a fairly high disease problem in Indonesia. The purpose of this study was to determine the relationship of cigarette smoke to the occurrence of hypertension in pregnant women in Brangkal Village, Kepohbaru District, Bojonegoro City. This study is an observational analytic study and uses a quantitative approach. The design of this study uses cross sectional. The location of this study was conducted in Brangkal Village, Kepohbaru District, Bojonegoro City, from July to August 2018. The sample in this study used a total sampling of the population of all pregnant women in Brangkal Village, namely 10 pregnant women. The results of the study here are from the calculation of the chi-square test above indicating that the root problem of cigarette smoke in hypertension has P Value <α so that the results obtained are Ho accepted or not significant (p = 0.857). The conclusion of this study is that there is no significant relationship to exposure to cigarette smoke in the incidence of hypertension in pregnant women. This occurs due to several factors such as a husband who is working outside the city so that exposure to cigarette smoke is not as often as possible. Supporting factors are such as diet, knowledge and the amount of parity can affect hypertension in pregnant women.